2009
DOI: 10.1007/s11060-009-9836-1
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of LRIG1 suppresses malignant glioma cell growth by attenuating EGFR activity

Abstract: Activated epidermal growth factor receptor (EGFR) has emerged as an important therapeutic target for a variety of solid tumors, particularly malignant gliomas. A recently discovered transmembrane glycoprotein, LRIG1, antagonizes the activity of epidermal growth factor receptor family receptor tyrosine kinases and acts as a negative feedback loop of EGFR and proposed tumor suppressors. The aim of this study was to investigate the impact of LRIG1 on the biological features of glioma cells and the possible mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 29 publications
3
43
2
Order By: Relevance
“…LRIG1 is a negative regulator of RTKs that enhances receptor ubiquitination and degradation 15,40,41. In the resistant cell line, the expression of EGFR and c-Met increased compared to the U251 cells, and LRIG1 expression was negatively correlated with the expression of EGFR and c-Met.…”
Section: Discussionmentioning
confidence: 99%
“…LRIG1 is a negative regulator of RTKs that enhances receptor ubiquitination and degradation 15,40,41. In the resistant cell line, the expression of EGFR and c-Met increased compared to the U251 cells, and LRIG1 expression was negatively correlated with the expression of EGFR and c-Met.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that LRIG1 was frequently decreased in gliomas (21), and the expression level of LRIG1 is significantly correlated with the malignancy of glioma (21,33). It has also been reported that upregulation of LRIG1 expression suppresses malignant glioma cell growth and induces cell apoptosis (21,(34)(35)(36), whereas downregulation of LRIG1 expression promotes the proliferation and aggressive properties of glioma cells (37,38). Furthermore, previous studies have suggested that LRIG1 is associated with the regulation of chemosensitivity of human cancer cells (39,40).…”
Section: Discussionmentioning
confidence: 94%
“…Leucine-rich repeats and immunoglobulin-like domains protein 1 (LRIG1) is considered to be a tumor suppressor in various types of cancer and is frequently downregulated in gliomas (18)(19)(20)(21). Therefore, the present study elucidated whether LRIG1 is a novel direct target by which miR-590-3p exerts its effect on radiosensitivity, as LRIG1 is predicted to be a target of miR-590-3p (http://www.microrna.org/microrna/home.do) and the expression of LRIG1 is associated with radiosensitivity in human glioblastoma (22).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of LRIG1 suppresses U251 malignant glioma cell migration and invasion by reducing MMP2/9 level 50. Besides, LRIG1 inhibits phosphorylation of MAPK, EGFR and AKT signalling molecules and affects biological behaviours including migration and invasion by inactivation of EGFR/AKT signalling pathway 51, 52. Thus, the other alternative pathway that MiR‐19 promoting glioma migration might by directly inhibiting LRIG1 expression and indirect activation of EGFR/AKT signalling pathway.…”
Section: Mir‐19 In Gliomamentioning
confidence: 99%